Impact of Inclusive University Programs on the Development of Socio-Emotional Skills and Functional Autonomy in Students with Mild Cognitive Disabilities - Suárez-Carreño, Franyelit; Pinto-Pomadera, Hilda; Trujillo-Zeballos, Omar Emilio; Calizaya-Lopez, Jose (Journal of Intellectual Disability - Diagnosis and Treatment, 2026)
Background: Inclusive higher education has emerged as a critical pathway for strengthening functional independence and social integration among students with mild cognitive disabilities. Although access to university programs has expanded, empirical evidence on the effectiveness of inclusive educational interventions in promoting socio-emotional skills and functional autonomy remains limited. This study examined the impact of university-based inclusive programs on these key developmental outcomes. Methods: A quantitative cross-sectional study design was used. Data were collected from final-year university students with mild cognitive disabilities who had participated in structured inclusive programs. A validated Likert-type questionnaire was used to measure socio-emotional skills and functional autonomy. Descriptive statistics were used to assess overall trends, while inferential analyses, including independent-samples t-tests and multiple regression, were conducted to examine group differences and predictive relationships. Results: The findings indicated that inclusive university programs were associated with improvements in socio-emotional competencies, including self-regulation, interpersonal interaction, and decision-making, as well as in functional autonomy related to academic and everyday activities. However, the regression analysis showed that these variables did not significantly predict overall perceived program effectiveness, suggesting the influence of additional contextual and institutional factors. Conclusions: University-based inclusive programs contribute positively to the development of socio-emotional skills and functional autonomy among students with mild cognitive disabilities. Nevertheless, their overall effectiveness appears to depend on a broader, integrative framework that includes academic support, social inclusion, and institutional resources. These findings provide relevant evidence for strengthening inclusive practices and policies in higher education.